Solution-focused brief counseling in reducing the negative impact of problematic online game use - Mulawarman, Mulawarman; Hariyadi, Sigit; Nugraheni, Edwindha Prafitra; Antika, Eni Rindi; Soputan, Shania Dea Menany (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
The study purposed to examine the effectiveness of the solution-focused brief counseling (SFBC) intervention to reduce the negative impacts of problematic online games use (POGU) in college students. The research subjects were chosen by purposive sampling method of students who have problems with online games at the Universitas Negeri Semarang (UNNES). The study was conducted with an embedded experimental research design in which the data was obtained using a quantitative approach. POGU and online addiction games were included in the characteristics of people with internet addiction (IA) based on the diagnostic and statistical manual of mental disorders, fourth edition (DSM-IV) criteria that have a negative impact. Based on the study, negative effects of playing online games included low self-control, not being able to reduce the length of time playing online games and having thoughts (preoccupation cognitive) that could not be controlled and weakening the brain work systems causing the online game addicts. The form of intervention used in the study was SFBC. The SFBC stages carried out included building relationships, identifying complaints that could be resolved, setting goals, designing, and implementing interventions, termination, evaluation, and follow-up.